Marine and Land Based Arduino Boat (International Journal of Innovative Research in Computer Science & Technology, 2021)
Disasters are natural calamities which  takes place accordingly across the world. Recently, in  2020, various disasters took place which affected the  world in various scenarios. During these situations,  emergency conditions take place which needs to be  handled timely and carefully. So, if any technology  contributes to these situations, proves to be a “Boon” for  the world. To improve the performance of a vehicle  designing is the important aspect for it. At the point when  the vehicle runs over a channel at a fast pace, the medium  will go along the vehicle in term of obstruction. The  reason behind the vehicle going in the opposite direction,  when the vehicle moves in at high velocity is because of  the structure of the room as there is air space density  inside the room. Other than that, the blueprint of the  vehicle ought to have an air of fascination with  individuals who look at everything about plan as far as  inventiveness and aesthetical worth. The land and/or  water capable automobile is a double reason vehicle  which is described by velocity and intangibility on water,  potability, and adaptability ashore and exceptional traffic  flow capacity at the intersection of land and water. This  project aims to make an Arduino based boat cum car  which can highly contribute to disasters. The project  would work both as a boat on one side and as a car on  other side. These technologies can help people in various  ways, for example, rescue operations, essentials delivery,  roads having large distance than water and many more.  People can use this technology according to the  requirement, as a boat or as a car, as and when required.
Keywords: Disasters; Arduino Boat; Marine Boat; Rescue Operations